Low birth weight among neonates in rural areas of Indonesia: A secondary data analysis - Nelwati Nelwati; Hema Malini; Ferry Efendi; Heri Kuswanto; Eka Misbahatul Mar’ah Has; Mahendra Tri Arif Sampurna (Belitung Nursing Journal, 2026)
Background: Low birth weight (LBW) is a major global health concern because of its strong association with infant mortality, morbidity, and impaired long-term development. The determinants of LBW among neonates in rural areas of Indonesia remain underexplored. Objective: To examine the prevalence of LBW and determine its associated factors among neonates in rural areas of Indonesia.   Methods: A cross-sectional study used secondary data sources from the 2017 Indonesian Demographic and Health Survey. A total of 6,701 mothers who lived in rural areas were included. Explanatory variables were maternal age, maternal education, smoking status, parity, birth interval, twin history, antenatal care (ANC), husband support, wealth quintile, region of residence, and complications during pregnancy. The outcome variable was the prevalence of LBW. Data were analyzed using bivariate analysis with a Chi-square test (χ2) and multivariable logistic regression. Results: The prevalence of LBW was 6.65%. First birth [AOR = 1.486; 95% CI: 1.126-1.959], twin history [AOR = 27.165; 95% CI = 13.006-56.738], fewer than four ANC visits [AOR = 2.193; 95% CI = 1.519-3.164], and complications during pregnancy [AOR = 1.890; 95% CI = 1.427-2.503] were significantly associated with the prevalence of LBW. Conclusion: This study revealed the prevalence of LBW among neonates in rural areas of Indonesia. First birth, twin history, ANC visits, and complications during pregnancy were significantly associated with LBW. It is suggested that health professionals should strengthen the quality of antenatal care and improve health promotion and education during pregnancy for rural mothers to reduce the prevalence of LBW.